2016
DOI: 10.1021/acs.chemrestox.6b00394
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Tobacco Carcinogen 2-Amino-9H-pyrido[2,3-b]indole (AαC) in Primary Human Hepatocytes

Abstract: 2-Amino-9H-pyrido[2,3-b]indole (AαC) is the most abundant carcinogenic heterocyclic aromatic amine (HAA) formed in mainstream tobacco smoke. AαC is a liver carcinogen in rodents, but its carcinogenic potential in humans is not known. To obtain a better understanding of the genotoxicity of AαC in humans, we have investigated its metabolism and its ability to form DNA adducts in human hepatocytes. Primary human hepatocytes were treated with AαC at doses ranging from 0.1 to 50 μM and the metabolites were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
(182 reference statements)
1
14
0
Order By: Relevance
“…19,20 These results signify that both AαC and 4-ABP are efficiently N -hydroxylated in human liver. AαC undergoes extensive metabolism by primary human hepatocytes to produce multiple phase I and phase II metabolites, 66 whereas the pathways of metabolism of 4-ABP in human hepatocytes are not well characterized. 20 On the basis of our understanding of 4-ABP metabolism in rodent and canine models, 32,6769 we surmise that the amount of HONH-4-ABP circulating in blood and delivered to the erythrocyte is far greater than that of HONH-AαC, resulting in proportionately higher levels of 4-ABP-Hb adducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 These results signify that both AαC and 4-ABP are efficiently N -hydroxylated in human liver. AαC undergoes extensive metabolism by primary human hepatocytes to produce multiple phase I and phase II metabolites, 66 whereas the pathways of metabolism of 4-ABP in human hepatocytes are not well characterized. 20 On the basis of our understanding of 4-ABP metabolism in rodent and canine models, 32,6769 we surmise that the amount of HONH-4-ABP circulating in blood and delivered to the erythrocyte is far greater than that of HONH-AαC, resulting in proportionately higher levels of 4-ABP-Hb adducts.…”
Section: Discussionmentioning
confidence: 99%
“…37 We previously reported that DNA adducts of AαC are formed at higher levels than the adducts formed with 4-ABP, PhIP and MeIQx in human T lymphocytes in vitro ; however, the DNA adducts are only detected in lymphocytes pre-activated with PMA/Ionomycin or CD3/CD28, which induce the expression of functional CYP1 activity for bioactivation. 76 Therefore, the capacity of cytochrome P450 enzymes expressed in peripheral WBC may be insufficient to N -hydroxylate 4-ABP and AαC. Alternatively, the phase II enzymes such as N -acetyltransferases (NAT) and sulfotransferases (SULT), which bioactivate HONH-4-ABP and HONH-AαC to the penultimate species that form DNA adducts, 48,77 may be expressed at insufficient levels in WBC to catalyze DNA binding of the N -hydroxylated metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio for the other HAAs ranges from 38,8% to 55,8%. MeIQx and PhIP have a relatively high ratio of metabolites reactive to DNA (45,2% and 44,5%) while AαC has a lower ratio (38,8%) in spite of its known higher reactivity towards DNA compared with MeIQx or PhIP [14]. This observation might be related to its smallest map of metabolism (average and median of numbers of metabolites and reactions in the map).…”
Section: Definition and Construction Of Enriched Metabolic Mapsmentioning
confidence: 97%
“…The size of these maps could be explained by the chemical structure of both HAAs that have few sub-structures on which SyGMa transformation rules can be applied. The maps predicted for two of the three well characterized HAAs in primary human hepatocytes [11,12,14], MeIQx -155 metabolites -and PhIP -128 metabolites, have a medium size. On the contrary, AαC, the third one, is associated with one of the smallest metabolic map.…”
Section: Definition and Construction Of Enriched Metabolic Mapsmentioning
confidence: 99%
See 1 more Smart Citation